The Presynaptic Microtubule Cytoskeleton in Physiological and Pathological Conditions: Lessons from Drosophila Fragile X Syndrome and Hereditary Spastic Paraplegias - Bodaleo, Felipe J.; Gonzalez-Billault, Christian (Frontiers in Molecular Neuroscience, 2016)
The capacity of the nervous system to generate neuronal networks relies on the establishment and maintenance of synaptic contacts. Synapses are composed of functionally different presynaptic and postsynaptic compartments. An appropriate synaptic architecture is required to provide the structural basis that supports synaptic transmission, a process involving changes in cytoskeletal dynamics. Actin microfilaments are the main cytoskeletal components present at both presynaptic and postsynaptic terminals in glutamatergic synapses. However, in the last few years it has been demonstrated that microtubules (MTs) transiently invade dendritic spines, promoting their maturation. Nevertheless, the presence and functions of MTs at the presynaptic site are still a matter of debate. Early electron microscopy (EM) studies revealed that MTs are present in the presynaptic terminals of the central nervous system (CNS) where they interact with synaptic vesicles (SVs) and reach the active zone. These observations have been reproduced by several EM protocols; however, there is empirical heterogeneity in detecting presynaptic MTs, since they appear to be both labile and unstable. Moreover, increasing evidence derived from studies in the fruit fly neuromuscular junction proposes different roles for MTs in regulating presynaptic function in physiological and pathological conditions. In this review, we summarize the main findings that support the presence and roles of MTs at presynaptic terminals, integrating descriptive and biochemical analyses, and studies performed in invertebrate genetic models.